2013
DOI: 10.1002/da.22141
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper Training for Suicide Prevention in First Nations Community Members: A Randomized Controlled Trial

Abstract: The lack of efficacy of ASIST in a First Nations on-reserve sample is concerning in the context of widespread policies in Canada on the use of gatekeeper training in suicide prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 23 publications
1
57
0
1
Order By: Relevance
“…The primary outcome would be assessed using The Suicide Intervention Response Inventory-2 (SIRI-2) [39] at baseline, post-intervention and 6 months follow up. Secondary outcomes would include self-reported preparedness measures [40], GPs attitudes (Attitudes Towards Suicide [41] and confidence (using the 5-item STORM confidence in the assessment and management of suicidal people scale) [22]; service user satisfaction using qualitative interviews; and, cost-effectiveness. If the effectiveness and cost-effectiveness of the e-CDSS is established, then this research could lead to improved assessment and management of suicidality in primary care and better patient experience of primary care mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome would be assessed using The Suicide Intervention Response Inventory-2 (SIRI-2) [39] at baseline, post-intervention and 6 months follow up. Secondary outcomes would include self-reported preparedness measures [40], GPs attitudes (Attitudes Towards Suicide [41] and confidence (using the 5-item STORM confidence in the assessment and management of suicidal people scale) [22]; service user satisfaction using qualitative interviews; and, cost-effectiveness. If the effectiveness and cost-effectiveness of the e-CDSS is established, then this research could lead to improved assessment and management of suicidality in primary care and better patient experience of primary care mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that gatekeeper training is not a 'one size fits all' may have relevance to minority groups. Lower levels of satisfaction and poorer outcomes, including a concerning increase in suicidal ideation among First Nations tribal community members in Canada, raises concern about appropriateness of standardized training for minority groups [22]. The issue of culture was raised by other researchers [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…In Manitoba, Canada, a randomized-controlled study of gatekeeper training found increased suicidal ideation occurred among First Nations tribal community members [22]. One group (n=31) received two days of Applied Suicide Intervention Skills Training (ASIST) and another group (n=24) attended a Resilience Retreat without focus on suicide awareness.…”
Section: Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our satisfaction and outcome variables were also subjective (e.g., attitudes) and we do not know to what extent they would correlate with more-objective assessments of training outcomes (e.g., intervention skill) or client outcomes. Also, while prior studies report the validity of retrospective surveys [14][15][16][17][18], a "true" baseline survey was not administered prior to the training. Finally, we only trained two coders to monitor fidelity and adherence.…”
Section: Limitationsmentioning
confidence: 99%